"You're such a pain!": Investigating how psychological pain influences the ostracism of a burdensome group member. (June 2020) - Wirth, James H.; LeRoy, Angie S.; Bernstein, Michael J.
Maintaining social relationships with others is essential for survival, but not all relationships are beneficial. Individuals exclude nonbeneficial burdensome group members, those who encumber group success. We investigated whether feeling psychological pain is a mechanism that prompts assessment of social threats―potentially putting the "brakes" on burdensome (nonbeneficial) relationships. Specifically, we investigated if interacting with burdensome individuals caused others to experience psychological pain, negative affect, and to dislike the burdensome individual. Across 5 studies, using 3 different paradigms, we found those who interacted with a burdensome individual experienced psychological pain, which influenced ostracizing (excluding and ignoring) the burdensome group member. In Studies 4 and 5, we found psychological pain mediated the relationship between burdensomeness and ostracism even when we accounted for negative affect and dislike of the burdensome individual. Our results suggest psychological pain can guide social interactions and should be the subject of future research involving social threat.